Model Pengembangan Ekonomi Kreatif Bagi Usaha Mikro Kecil dan Menengah di Tengah Ancaman Resesi Ekonomi Berdasarkan Syirkah Mudharabah - Dyah Ochtorina Susanti (Faculty of Law, Universitas Pattimura, 2022)
This research is motivated by the existence of a recession in Indonesia, where the recession affects and has an impact on economic activity, such as a decrease in investment, the level of production or commodities, an increase in unemployment, an increase in prices for goods in general (inflation), a reduction in subsidies and government funding, and a decrease purchasing power and public consumption, which of course also has an impact, especially on Micro, Small, and Medium Enterprises (MSME). In this regard, it is necessary to develop MSME in the midst of the threat of an economic recession, one of which is through business cooperation based on syirkah mudharabah. Research that uses the normative legal research with the statute approach, and conceptual approach, results in findings, namely the concept or model of creative economic development for MSME in the midst of an economic recession based on syirkah mudharabah. This model is expected to be used by business actors to develop MSME amid the Covid-19 pandemic.